PEDAGOGICAL CONDITIONS FOR DEVELOPING LEGAL COMPETENCE IN STUDENTS BASED ON EDUCATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article investigates the pedagogical conditions that are necessary and sufficient for the systematic development of legal competence in secondary school students within the framework of the "Education" (Tarbiya) subject in Uzbekistan. Drawing on curriculum analysis, pedagogical theory, and empirical observations from general secondary education institutions, the study argues that legal competence cannot be cultivated through incidental or implicit instruction alone. Rather, it requires a deliberately structured, values-integrated, and methodologically diverse pedagogical environment. The article identifies six core pedagogical conditions — curricular integration, value coherence, interactive methodology, digital augmentation, institutional partnership, and systematic assessment — and examines how each condition, and their combined synergistic effect, contributes to the formation of legally conscious, civically active, and morally grounded young citizens. Practical recommendations for curriculum designers, subject teachers, and educational administrators are offered, grounded in the realities of the Uzbek educational context.